Encyclopedia of Criminology and Criminal Justice
311 illus., 156 illus. in color. eReference.
Keywords: The Encyclopedia of Criminology and Criminal Justice is an international, comprehensive reference tool for the field of Criminology and Criminal Justice that is both cutting edge as well as of very high scientific quality and prestige. This 10-volume work provides a complete and systematic coverage of the field that is unprecedented. The Encyclopedia "defines the field" through its choice of organization and entries. It identifies and brings emerging ideas and trends to the forefront. The Encyclopedia covers Criminology and Criminal Justice in ten broad areas, with leading researchers writing substantive contributions within their area of expertise: Corrections and Criminal Justice Supervision in the Community Courts, Sentencing and the Judicial System Crimes, Criminals and Victims Crime Places and Situations Explanations for Criminal Behavior Forensic Science Data, Methods, and Statistics Police and Law Enforcement Psychology of Law Social Interventions and Prevention This work features approximately 600 entries, organized in alphabetical order. The work is comprised under the direction of two Editors-in-Chief in consultation with 12 Associate Editors and more than 180 Area Editors. It is an essential and dynamic reference for researchers in the fields of Criminology and Criminal Justice, as well as useful a research tool for those in related fields of the social and behavioral sciences.